2022
DOI: 10.31234/osf.io/2gswt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infant-Directed Speech Does Not Always Involve Exaggerated Vowel Distinctions: Evidence From Danish

Abstract: The phonological peculiarities of spoken Danish have been argued to reduce the salience of cues that allow infant listeners to extract linguistic information from the speech stream. To assess whether caregivers adjust their infant-directed speech to accommodate these processing challenges, this study compares the acoustic properties of 26 Danish caregivers’ spontaneous speech when interacting with their 11-24-month-old infants (i.e., infant-directed speech, IDS) and when interacting with an adult experimenter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 125 publications
1
10
0
Order By: Relevance
“…As all the study methods were comparable, these varied findings suggest that vowel hyperarticulation in IDS might not be a universal phenomenon. Further studies employing different methods than Kuhl et al (1997) (e.g., inclusion of more than three vowels, inclusion of vowels other than corner vowels, IDS recorded during reading sessions, Benders et al, 2013;Cox et al, 2022;Englund & Behne, 2006) also provide conflicting findings regarding the presence of vowel hyperarticulation in IDS.…”
Section: Vowel Hyperarticulation In Infant-directed Speech Vowel Hype...mentioning
confidence: 99%
“…As all the study methods were comparable, these varied findings suggest that vowel hyperarticulation in IDS might not be a universal phenomenon. Further studies employing different methods than Kuhl et al (1997) (e.g., inclusion of more than three vowels, inclusion of vowels other than corner vowels, IDS recorded during reading sessions, Benders et al, 2013;Cox et al, 2022;Englund & Behne, 2006) also provide conflicting findings regarding the presence of vowel hyperarticulation in IDS.…”
Section: Vowel Hyperarticulation In Infant-directed Speech Vowel Hype...mentioning
confidence: 99%
“…A growing body of research, using advanced acoustic analyses, provides evidence against the hypothesis of enhanced clarity of IDS, implying that the traditionally reported vowel space area may be a too crude proxy for the 'clear speech' claim. Vowel categories in IDS appear to be less distinctive, as compared to ADS: they are separated by smaller acoustic distances (Cristia & Seidl, 2014;Cox et al, 2022b), and spectral differences between them are reduced (Martin et al, 2015). In addition, vowels in IDS appear to be more variable, as revealed by larger within-category variability (Cristia & Seidl, 2014;Englund, 2018;McMurray et al, 2013;Miyazawa et al, 2017;Rosslund et al, 2022) and larger change in the spectral dynamics over the vowel duration (Miyazawa et al, 2017).…”
Section: Is (Mothers') Ids Really Providing a Clearer Input To The Ch...mentioning
confidence: 99%
“…Further, our results revealed that parents expanded their vowel space in IDS, both when measuring the full vowel space, and with the three most extreme corner vowels in Norwegian (/i/-/ae/-/u/), and that their vowel categories were more variable and less distinct in IDS than ADS. Hence, while IDS certainly features more exaggerated prosody and might function as a 'perceptual hook', vowel categories were more variable when compared to ADS (see also Cristia & Seidl, 2014;Cox et al, 2022b;Miyazawa et al, 2017;Rosslund et al, 2022), and hence may not provide a cleaner acoustic input to the child.…”
Section: Properties Of Mother's and Father's Idsmentioning
confidence: 99%
“…However, the extent to which they vary and adapt to different contextual constraints (e.g., a casual chat vs. reaching a joint decision at work vs. helping a child in developing their language) is only now starting to be systematically investigated (Colman & Healey, 2011; Cox et al., 2022a, 2022b; Dideriksen, Christiansen, Tylén, Dingemanse, & Fusaroli, 2023; Healey, Purver, & Howes, 2014). Similarly, while it is acknowledged that cross‐linguistic and cross‐cultural variations play a crucial role in human behavior and cognition (Christiansen, Contreras Kallens, & Trecca, 2022; Cox et al., 2022a, 2022b; Henrich, Heine, & Norenzayan, 2010; Trecca, Tylén, Højen, & Christiansen, 2021), very little is known about how conversational dynamics systematically vary and adapt to diverse languages and cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of mutual understanding are an integral part of how we understand human cognition in context (e.g., Dale, Fusaroli, Duran, & Richardson, 2013; Fusaroli, Demuru, & Borghi, 2012; Schilbach et al., 2013), and are becoming crucial components in the development of human–computer interfaces (Loth, Jettka, Giuliani, & De Ruiter, 2015; Sugiyama, Meguro, Yoshikawa, & Yamato, 2018), and clinical assessments of social functioning (Dwyer, David, McCarthy, McKenna, & Peters, 2019; Hopkins, Yuill, & Keller, 2016; Schilbach et al., 2013). However, the extent to which they vary and adapt to different contextual constraints (e.g., a casual chat vs. reaching a joint decision at work vs. helping a child in developing their language) is only now starting to be systematically investigated (Colman & Healey, 2011; Cox et al., 2022a, 2022b; Dideriksen, Christiansen, Tylén, Dingemanse, & Fusaroli, 2023; Healey, Purver, & Howes, 2014). Similarly, while it is acknowledged that cross‐linguistic and cross‐cultural variations play a crucial role in human behavior and cognition (Christiansen, Contreras Kallens, & Trecca, 2022; Cox et al., 2022a, 2022b; Henrich, Heine, & Norenzayan, 2010; Trecca, Tylén, Højen, & Christiansen, 2021), very little is known about how conversational dynamics systematically vary and adapt to diverse languages and cultures.…”
Section: Introductionmentioning
confidence: 99%